Photo-crosslinking: An emerging strategy for improving the performance of biopolymer-based food packaging - Hankai Zhang; Heyujia Zhang; Yuhe Dong; Xi Yu; Ying Xiao; Weizheng Sun; Chun Feng; Xiaoyu Huang; Tian Zhong (Trends in Food Science & Technology, 2026)

The “Bridge” between hydrophobic active substances and hydrophilic biopolymers: The role of cyclodextrins in enhancing the properties of food packaging films - Zhenzi Yun; Yuhe Dong; Ziyu Liu; Xi Yu; Ying Xiao; Qianrong Fang; Tian Zhong (Trends in Food Science & Technology, 2026)

Carbon amendment drives microbial community to favor dissimilatory nitrate reduction to ammonium over denitrification in paddy soil - Mingzi Shi; Sen Zhang; Kejia Yu; Yuqi Zhang; Yikai Zhou; Yicai Yao; Wang Zhou; Yuhe Wang; Hongge Chen; Mingdao Wang (European Journal of Soil Biology, 2026)

The critical trigger of 2-methylisoborneol in Taihu Lake: Flow velocity - Huixian Li; Yuan Xiao; Xujie Shi; Denghui Wang; Lei Li; Shuili Yu; Yuhe He; Jianhua Li; Changtao Yang; Yuwei Tao; Qi Yin (Water Research, 2026)

Preparation of gelatin/sodium carboxymethyl cellulose-based probiotic controlled-release tablets via complex coacervation and the double emulsification method - Yu Wang; Yuhe Dong; Bingmin Wu; Yao Liu; Zhenzi Yun; Xi Yu; Quancai Sun; Ying Xiao; Tian Zhong (Food Hydrocolloids, 2026)

A self-assembled perovskite composite air electrode for intermediate-temperature solid oxide electrochemical cells - Zhuo Cheng; Fan He; Kang Xu; Feng Zhu; Xirui Zhang; Yangsen Xu; Yuhe Liao; Li Zhang; Yu Chen (Chemical Engineering Journal, 2026)

Dietary polysaccharides from Ulva prolifera enhance growth, antioxidant capacity, immune response, and intestinal health in orange-spotted grouper (Epinephelus coioides) - Minhui Yu; Yulei Kou; Tian Xu; Honglin Li; Ao Jian; Xinyue Yang; Yuhe Shen; Zheng Zheng; Chunxiang Ai (Journal of Applied Phycology, 2026)

Pectin-coated liposomes for pectinase-triggered thymol release: A novel on-demand sterilization approach for orange preservation - Zikai Li; Yuhe Dong; Tong Wu; Wanying Zhu; Haohan Jing; Tao Jiang; Yao Liu; Xi Yu; Ying Xiao; Tian Zhong (Food Hydrocolloids, 2026)

Decline Trends of Chlorophyll-a in the Yellow and Bohai Seas over 2005–2024 from Remote Sensing Reconstruction - Yuhe Tian; Jun Song; Junru Guo; Yanzhao Fu; Yu Cai (Journal of Marine Science and Engineering, 2025)
Chlorophyll-a (Chl-a) concentration is a key indicator of coastal ecosystem health, reflecting both primary productivity and the ecosystem’s response to climate change and human activities. This study quantifies long-term Chl-a trends in the Yellow and Bohai Seas using a multi-source remote sensing reconstruction dataset generated with deep learning algorithms. Quantile regression was applied to assess changes across the 75th, 50th, and 25th percentiles, and environmental drivers—including sea surface temperature, mixed layer depth, wind speed, and sea surface height anomalies—were evaluated in representative regions such as estuaries, aquaculture zones, and offshore waters. From 2005 to 2024, Chl-a concentrations declined across the 75th, 50th, and 25th percentiles, with rates of −4.82 × 10−3, −4.50 × 10−3, and −4.09 × 10−3 mg·m−3·a−1, respectively (where “a” denotes year). The decline also showed strong seasonal differences, with summer decreases (−0.0638 mg·m−3·a−1) substantially greater than winter (−0.04 mg·m−3·a−1). Spatially, the decline was more pronounced in high-concentration nearshore waters, with rates of −0.0283 mg·m−3·a−1 in the Qinhuangdao region, compared to −0.0137 mg·m−3·a−1 in deeper offshore waters. Mixed-layer depth and wind speed emerged as the primary physical controls, with nearshore declines driven by enhanced vertical mixing and offshore changes dominated by mesoscale oceanic processes. These findings provide new insights for modeling and managing coastal ecosystems under combined climate and anthropogenic pressures.

EASNet: Edge-aware Segmentation Network for Skin Lesion Segmentation with Boundary-aware and Frequency Attention Mechanisms - Junwei Yu; Yuhe Xia; Jianping Li; Nan Liu; Haoze Li; Weiya Shi (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Dynamic covalent assembly of hierarchical COF hollow fibers for selective dye remediation - Huiling Chen; Xiubei Yang; Guiping Yang; Yuhe Mu; Chengbing Yu; Wei Zhang; Gaofeng Zeng (Desalination, 2025)

Food contact materials based on N-halamines or photosensitizers: An emerging strategy for developing “rechargeable” antibacterial properties - Yao Liu; Hankai Zhang; Zhou Zhang; Yuhe Dong; Tao Jiang; Yujia Zhang; Ye Peng; Xi Yu; Ying Xiao; Tian Zhong (Trends in Food Science & Technology, 2025)

Bacteria-triggered on-demand thymol release for salmon preservation: A self-destructive antibacterial strategy - Yuhe Dong; Xiaohui Jia; Tong Wu; Wanying Zhu; Zhou Zhang; Tao Jiang; Xi Yu; Ying Xiao; Chun Feng; Xiaoyu Huang; Tian Zhong (Food Chemistry, 2025)

Genistein mitigates renal fibrosis in diabetic nephropathy by suppressing epithelial–mesenchymal transition and aberrant glycolysis through downregulating the expression of HIF-1α - Tao Jiang; Yuhe Dong; Liang Wang; Tong Wu; Xi Yu; Ying Xiao; Tian Zhong (Food Bioscience, 2025)

Anammox and denitrifying bacteria and their nitrogen removal potential in lake sediments mediated by environmental changes - Mamun Abdullah Al; Yunfeng Wang; Jie Huang; Yuhe Yu; Philippe Juneau; Zhili He; Qingyun Yan (Marine Life Science & Technology, 2025)

Mesoporous high-entropy-alloy electrocatalysts via electrospinning for enhanced alkaline water electrolysis - Lu Wang; Chuhao Wang; Yuhe Mu; Jingrui Fan; Xiubei Yang; Chengbing Yu; Bing Guo; Gaofeng Zeng (Fuel, 2025)

Preparation of 3D printable pickering emulsion gels using corn oligopeptide/xanthan gum complexes - Zihan Zheng; Yuhe Ma; Jinxin Jiang; Wei Yang; Wuyin Weng; Linfan Shi; Yue Yu; Zhanming Li; Zhongyang Ren (Food Hydrocolloids, 2025)

A perovskite-type air electrode with in situ formed BaCoO3-δ nanoparticles for reversible protonic ceramic electrochemical cells - Wanqing Deng; Yangsen Xu; Xirui Zhang; Kang Xu; Yuhe Liao; Xuan Yang; Yu Chen (Chemical Engineering Journal, 2025)

Improving the emulsification properties of corn starch by esterification combined with freeze-thawing and enzymatic treatment - Run Ji; Jieli Xu; Yuhe Yu; Shuang Song; Xiuling Zhang; Wentao Zhang (Food Chemistry, 2025)

Responses of nitrogen conversion, related enzyme activity, and microbial community to soil hypoxia in a simulated Phyllostachys praecox forest with mulching - Yuhe Zhang; Yunfei Yu; Shunyao Zhuang (Journal of Soils and Sediments, 2025)

Effect of co-pigments on anthocyanins of wild cranberry and investigation of interaction mechanisms - Shuang Song; Yuhe Yu; Shengzhao Song; Xiuling Zhang; Wentao Zhang (Food Chemistry, 2025)

Mechanisms by which Ganglioside GM1, a specific type of glycosphingolipid, ameliorates BMAA-induced neurotoxicity in early-life stage of zebrafish embryos - Yanjun Liu; Yuhe Zhu; Xiaoxu Wang; Yiyang Li; Shuaiqi Yang; Hongyan Li; Bo Dong; Zhigao Wang; Yu Song; Jie Xu; Changhu Xue (Food Research International, 2025)

Underlying mechanisms and molecular targets of genistein in the management of type 2 diabetes mellitus and related complications - Tao Jiang; Yuhe Dong; Wanying Zhu; Tong Wu; Linyan Chen; Yuantong Cao; Xi Yu; Ye Peng; Ling Wang; Ying Xiao; Tian Zhong (Critical Reviews in Food Science and Nutrition, 2024)

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

Transparent coating based on multienzyme-mimicking Janus nanozyme for synergetic biofouling control in seawater - Tao Yu; Jiangjiexing Wu; Yuhe Shen; Anastasia Penkova; Wei Qi; Rongxin Su (Chemical Engineering Journal, 2024)

Risk assessment of e-waste - Liquid Crystal Monomers re-suspension caused by coastal dredging operations - Chang He; Alessandro Stocchino; Yuhe He; Kenneth Mei Yee Leung; Francesco De Leo; Zhen-Yu Yin; Yin-Fu Jin (Science of The Total Environment, 2024)

Multiplex-PCR method application to identify duck blood and its adulterated varieties - Lijun Gao; Bingyang Du; Qiuhe Ma; Yuhe Ma; Wenying Yu; Tao Li; Yue Liu; Guangxin Yuan (Food Chemistry, 2024)

Evolution of dissolved organic nitrogen chemistry during transportation to the marginal sea: Insights from nitrogen isotope and molecular composition analyses - Zhenwei Yan; Yu Xin; Xiaosong Zhong; Yuanbi Yi; Penghui Li; Yuntao Wang; Yuping Zhou; Yuhe He; Chen He; Quan Shi; Wenqi Xu; Ding He (Water Research, 2024)

A review of natural plant extracts in beverages: Extraction process, nutritional function, and safety evaluation - Tong Wu; Wanying Zhu; Linyan Chen; Tao Jiang; Yuhe Dong; Letao Wang; Xinyang Tong; Hui Zhou; Xi Yu; Ye Peng; Ling Wang; Ying Xiao; et al. (Food Research International, 2023)

Host Habitat as a Dominant Role in Shaping the Gut Microbiota of Wild Crucian Carp (Carassius auratus) - Xinghao Li; Xueli Huang; Liya Zhao; Wei Cai; Yuhe Yu; Jin Zhang (Fishes, 2023)
Current knowledge on the fish gut microbiota has largely been obtained from experiments on laboratory-reared animals. Here, the crucian carp (Carassius auratus) with a mean weight of 159.9 ± 11.4 g (mean ± SD) were collected from their natural habitats (i.e., Wuhu lake and Poyang lake, China), and the gut microbiota were analysed by using the next-generation sequencing of 16S rRNA gene. We obtained more than 430,000 high-quality reads, which constituted more than 1200 operational taxonomy units (OTUs), revealing extremely diverse microbes in the fish gut. Proteobacteria, Fusobacteria, Bacteroidetes and Firmicutes were detected as the prominent phyla (each > 1% of total abundance) within the gut microbiota, regardless of the host habitat or the gut segment (i.e., foregut vs. hindgut). Although the microbes in the hindgut were more diverse (OTU number, Shannon and Chao1; One-way Anova, p > 0.05) than in the foregut, the host habitat had a significant role in shaping the community structures (MRPP, ANOSIM, PERMANOVA, p

Effect of gastrodin against cognitive impairment and neurodegeneration in APP/PS1 mice via regulating gut microbiota–gut–brain axis - Yuhe Zhang; Yan Chen; Shushu Yuan; Qingxia Yu; Jianjiong Fu; Luyun Chen; Jiaming Liu; Yuping He (Experimental Brain Research, 2023)

Biodegradation of the nitrile-containing insecticides sulfoxaflor, flonicamid, thiacloprid, and acetamiprid by immobilized Escherichia coli harboring genes of nitrile hydratase and a cobalt transporter - Huoyong Jiang; Huaxiao Li; Yuhe Wang; Xuexiu Yu; Xiaoyue Chen; Yijun Dai (Journal of Environmental Chemical Engineering, 2023)

Host–microbiota interactions and responses to grass carp reovirus infection in Ctenopharyngodon idellus - Fanshu Xiao; Lanjie Liao; Qiaoqing Xu; Zhili He; Tiaoyi Xiao; Jianjun Wang; Jie Huang; Yuhe Yu; Bo Wu; Qingyun Yan (Environmental Microbiology, 2021)
Summary Gut microbiota could facilitate host to defense diseases, but fish–microbiota interactions during viral infection and the underlying mechanism are poorly understood. We examined interactions and responses of gut microbiota to grass carp reovirus (GCRV) infection in Ctenopharyngodon idellus , which is the most important aquaculture fish worldwide. We found that GCRV infection group with serious haemorrhagic symptoms (G7s) showed considerably different gut microbiota, especially with an abnormally high abundance of gram‐negative anaerobic Cetobacterium somerae . It also showed the lowest ( p p Cetobacterium and Acinetobacter . The results suggested that an expansion of C. somerae initiated by GCRV could aggravate host inflammatory reactions through the LPS‐related NLRs and TLRs pathways. This study advances our understanding of the interplay between fish immunity and gut microbiota challenged by viruses; it also sheds new insights for ecological defense of fish diseases with the help of gut microbiota.

Spatio-temporal patterns of zooplankton in a main-stem dam affected tributary: a case study in the Xiangxi River of the Three Gorges Reservoir, China - Xinghao Li; Jie Huang; Sabine Filker; Thorsten Stoeck; Yonghong Bi; Yuhe Yu; Weibo Song (Science China Life Sciences, 2019)

Necessary Sequencing Depth and Clustering Method to Obtain Relatively Stable Diversity Patterns in Studying Fish Gut Microbiota - Fanshu Xiao; Yuhe Yu; Jinjin Li; Philippe Juneau; Qingyun Yan (Current Microbiology, 2018)

Comparative study on the gut microbiotas of four economically important Asian carp species - Xinghao Li; Yuhe Yu; Chang Li; Qingyun Yan (Science China Life Sciences, 2018)

Nearly a decade‐long repeatable seasonal diversity patterns of bacterioplankton communities in the eutrophic Lake Donghu (Wuhan, China) - Qingyun Yan; James C. Stegen; Yuhe Yu; Ye Deng; Xinghao Li; Shu Wu; Lili Dai; Xiang Zhang; Jinjin Li; Chun Wang; Jiajia Ni; Xuemei Li; et al. (Molecular Ecology, 2017)
Uncovering which environmental factors govern community diversity patterns and how ecological processes drive community turnover are key questions related to understand the community assembly. However, the ecological mechanisms regulating long‐term variations of bacterioplankton communities in lake ecosystems remain poorly understood. Here we present nearly a decade‐long study of bacterioplankton communities from the eutrophic Lake Donghu (Wuhan, China) using 16S rRNA gene amplicon sequencing with MiSeq platform. We found strong repeatable seasonal diversity patterns in terms of both common (detected in more than 50% samples) and dominant (relative abundance >1%) bacterial taxa turnover. Moreover, community composition tracked the seasonal temperature gradient, indicating that temperature is a key environmental factor controlling observed diversity patterns. Total phosphorus also contributed significantly to the seasonal shifts in bacterioplankton composition. However, any spatial pattern of bacterioplankton communities across the main lake areas within season was overwhelmed by their temporal variabilities. Phylogenetic analysis further indicated that 75%–82% of community turnover was governed by homogeneous selection due to consistent environmental conditions within seasons, suggesting that the microbial communities in Lake Donghu are mainly controlled by niche‐based processes. Therefore, dominant niches available within seasons might be occupied by similar combinations of bacterial taxa with modest dispersal rates throughout different lake areas.

Environmental filtering decreases with fish development for the assembly of gut microbiota - Qingyun Yan; Jinjin Li; Yuhe Yu; Jianjun Wang; Zhili He; Joy D. Van Nostrand; Megan L. Kempher; Liyou Wu; Yaping Wang; Lanjie Liao; Xinghao Li; Shu Wu; et al. (Environmental Microbiology, 2016)
Summary Gut microbiota typically occupy habitats with definable limits/borders that are comparable to oceanic islands. The gut therefore can be regarded as an ‘island’ for the assembly of microbial communities within the ‘sea’ of surrounding environments. This study aims to reveal the ecological mechanisms that govern microbiota in the fish gut ‘island’ ecosystem. Taxonomic compositions, phylogenetic diversity, and community turnover across host development were analyzed via the high‐throughput sequencing of 16S rRNA gene amplicons. The results indicate that the Shannon diversity of gut microbiota in the three examined freshwater fish species all significantly decreased with host development, and the dominant bacterial taxa also changed significantly during host development. Null model and phylogenetic‐based mean nearest taxon distance (MNTD) analyses suggest that host gut environmental filtering led to the assembly of microbial communities in the fish gut ‘island’. However, the phylogenetic clustering of local communities and deterministic processes that governed community turnover became less distinct as the fish developed. The observed mechanisms that shaped fish gut microbiota seemed to be mainly shaped by the gut environment and by some other selective changes accompanying the host development process. These findings greatly enhance our understanding of stage‐specific community assembly patterns in the fish gut ecosystem.

Diversity of nifH gene amplified from plankton-community DNA in a shallow eutrophic lake (Lake Donghu, Wuhan, China) - Qingyun Yan; Yuhe Yu; Weisong Feng (Limnology, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Metagenome-based analysis: A promising direction for plankton ecological studies - QingYun Yan; YuHe Yu (Science China Life Sciences, 2011)

Studies on the Toxic Effects of La3+ to Tetrahymena thermophila by Microcalorimetry - Chen Xiaojuan; Feng Weisong; Yu Yuhe; Wan Chengyan; Peng Jianhua (Biological Trace Element Research, 2008)

Preliminary study on applicability of microsatellite DNA primers from parasite protozoa Trypanosoma cruzi in free-living protozoa - Wenjing Zhang; Yuhe Yu; Yunfen Shen; Wei Miao; Weisong Feng (Journal of Ocean University of China, 2004)

Growth and production of free-living heterotrophic nanoflagellates in a eutrophic lake – Lake Donghu, Wuhan, China - Yufeng Zhao; Yuhe Yu; Weisong Feng; Yunfen Shen (Hydrobiologia, 2003)